Photophoretic Levitation: Photophoretic Levitation of Macroscopic Nanocardboard Plates (Adv. Mater. 16/2020). Issue 16 (21st April 2020) - Cortes, John; Stanczak, Christopher; Azadi, Mohsen; Narula, Maanav; Nicaise, Samuel M.; Hu, Howard; Bargatin, Igor
Abstract : In article number 1906878, Igor Bargatin and co‐workers demonstrate that centimeter‐scale hollow plates with nanoscale thickness and microscopic channels can levitate when illuminated with light intensity comparable to natural sunlight. Light‐driven thermal transpiration of air through the plate's channels creates air jets, which result in small‐height hovering at atmospheric pressure and mid‐air flight at reduced pressures, even allowing small payloads.